COMMERCIALIZATION OF CARBON CREDITS ON SMALL PROPERTIES - de Moura, Jadson Belem; de Souza, Rodrigo Fernandes; dos Santos, José Mateus; Filho, Luiz Cesar Lopes; Pires, Willian Marques; Ribeiro, Walber Alves (International Journal of Research -GRANTHAALAYAH, 2019)
Today the world has turned its attention to the phenomena of climate change on the planet. Excess emissions of greenhouse gases (GHG) from human activity are responsible for this change. Gases such as carbon dioxide (CO2), methane (CH4) and nitrous oxide (N2O) are part of GHG and have a large capacity to store the energy of the sun in the form of heat, increasing the average temperature in the atmosphere. After the Kyoto treaty, major powers pledged to reduce GHG emissions into the atmosphere, but this practice implies a slowdown in the industrialization and profits of these countries. Countries that can not or do not opt to reduce emissions can buy credits from nations that can generate extra emission reduction values, thus resulting in trade in these credits. Small properties have the potential for credit production, which can generate extra income for the small producer. Therefore, this work aimed at evaluating the potential of commercialization of carbon credits by small properties. The methodology of the work consisted in a systematic literature review on the current state of the art of the proposed theme.